Impacts of various shaped Cu-nanomaterial on the heat transfer over a bilateral stretchable surface: Numerical investigation. (December 2021) - Adnan,; Khan, Umar; Ahmed, Naveed; Manzoor, Raheela; Mohyud-Din, Syed Tauseef
The heat transport in the nanofluids attained much interest of the researchers and engineers due to broad uses in medical sciences, paint industries, aerodynamics, wheel alignment and manufacturing of aircraft parts. Therefore, keeping in mind the paramount significance of the heat transfer, the study of Cu-nanomaterials based nanofluid is conducted. The governing nanofluid model transformed in dimensionless version via similarity transformations. For numerical simulation of the dynamics of Cu-H2 O, RK technique with shooting algorithm is employed and presented behavior of the fluid motion, temperature, wall shear stresses and local thermal performance rate via graphical aid. It is noted that the heat transfer augmented promptly by increasingλ and volumetric fraction of Cu nanomaterial. Further, graphical and tabular comparison is also provided under certain assumptions which authenticate the study.